José María Otero de Navascués Enríquez de la Sota, Marqués de Hermosilla: The nuclear and scientific advantage of the Hispanic world during the Cold War - de Andrés Martín, Juan Ramón (Libros UAT, 2018)
José María Otero de Navascués Enríquez de la Sota, Marques de Hermosilla y Contralmirante Engineer of the Navy, of Navarre origin, was born in Madrid on March 16, 1907 and died in the same capital on March 9, 1983. He belonged to that generation Spanish that incorporated Spain into the universal scientific current. Author of many and remarkable research works on various points of geometric optics, physics, physiology and nuclear energy; Otero discovered nocturnal myopia in 1942. The issue of nighttime myopia was vital in World War II. In aerial combat, the pilot who before distinguished the enemy had a definite advantage, and the same happened at sea. In the visual acuity of the binoculars and periscopes was the key to everything. The importance of the finding was extraordinary because, had its discovery been known, 66% visual acuity could have been gained.